2023
DOI: 10.1111/jsr.13818
|View full text |Cite
|
Sign up to set email alerts
|

The promise of portable remote auditory stimulation tools to enhance slow‐wave sleep and prevent cognitive decline

Abstract: Dementia is the seventh leading cause of mortality, and a major source of disability and dependency in older individuals globally. Cognitive decline (and, to a lesser extent, normal ageing) are associated with sleep fragmentation and loss of slowwave sleep. Evidence suggests a bidirectional causal link between these losses.Phase-locked auditory stimulation has emerged as a promising non-invasive tool to enhance slow-wave sleep, potentially ameliorating cognitive decline. In laboratory settings, auditory stimul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In this study, our methodology has been applied to patients with childhood epilepsy, but the proposed methods are applicable to any disorder related to sleep or spike alterations (e.g., Alzheimer’s, Parkinson’s, autism, ADHD). A better understanding of the underlying pathology has become increasingly important in recent years, due to the rise of new technologies enabling us to manipulate sleep, such as acoustic stimulation 50 , which may lead to new treatment options for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our methodology has been applied to patients with childhood epilepsy, but the proposed methods are applicable to any disorder related to sleep or spike alterations (e.g., Alzheimer’s, Parkinson’s, autism, ADHD). A better understanding of the underlying pathology has become increasingly important in recent years, due to the rise of new technologies enabling us to manipulate sleep, such as acoustic stimulation 50 , which may lead to new treatment options for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using multiple nights of PLAS further confirmed a lack of physiological habituation, rendering PLAS a good candidate for long-term applications (Debellemaniere et al, 2018;Lustenberger et al, 2022). With current developments in the field of PLAS-capable home-use devices (Zeller et al, 2023), future research can delve into options for long-term PLAS-applications and investigate whether memory increases can be sustainable.…”
Section: Limitationsmentioning
confidence: 91%
“…This suggests that phase-locked acoustic stimulation in younger adults could be an effective tool to modulate memory retention. Toward this end, Wunderlin and colleagues compare portable systems that allow for multiple nights of electroencephalogram (EEG) recordings and phase-locked acoustic stimulation delivery with the goal of collecting quality data over multiple nights to strengthen future studies (Zeller et al, 2023). A meta-analysis by Stanyer and colleagues reports a memory performance effect size (d = 0.68, 95% CI [0.06, 1.30]) that is almost three-fold larger than reported for a similar set of studies in the meta-analysis by Wunderlin and colleagues.…”
Section: Figurementioning
confidence: 99%